Large-Scale Test Setup of Concrete Pavement Slabs Jointed by Carbon Fiber-Reinforced Polymer Dowel Bars as Load Transfer Devices - Taha Ahmed; Ahmad Saad; Abdulhadi Kazem; Ali Radwan; Ali AlMutairi; Sarah Ashkanani (Engineering Proceedings, 2023)
Conventional steel bars are mostly used as the main load transfer mechanism between jointed slabs in rigid pavements; however, they are generally prone to corrosion which reduces the load transfer efficiency at the joints. This study evaluates the performance of steel bars wrapped with Carbon Fiber Reinforced Polymer (CFRP) sheets, introducing a corrosion-free alternative to conventional steel bars while maintaining the required strength. This paper explains the test setup of large-scale shear strength and load transfer efficiency tests that are currently conducted on the slab samples to evaluate the structural performance of the proposed dowel bars and concrete mix designs.